Maternal resveratrol regulates the growth performance, antioxidant capacity, and intestinal health of suckling piglets through intestinal microorganisms at high summer temperatures - Zhao, Yi; Huang, Yujian; Gao, Kaiguo; Wen, Xiaolu; Hu, Shenglan; Wang, Li; Jiang, Zongyong; Xiao, Hao (Frontiers in Nutrition, 2022)
Background Resveratrol has numerous beneficial properties, including antioxidant, anti-inflammatory, and immunomodulatory properties. High summer temperatures in Southern China affect the reproductive performance of sows. The present study aimed to investigate the effects of dietary resveratrol supplementation in different thermal environments on the reproductive performance, antioxidant capacity, immune function, and intestinal microbes of sows and piglets during late gestation and lactation, as well as their relationship with colostrum immunoglobulin. Methods A two-phase experiment was conducted with 40 healthy multiparous sows. In the first phase of the experiment, 20 sows were used in a moderate temperature environment, and in the second phase of the experiment, the remaining 20 sows were used in a high-temperature environment. In both phases, sows were fed either a control diet or a diet consists of control diet and 300 mg/kg resveratrol starting on day 75 of gestation. Plasma, milk, and fecal samples were collected to obtain the indices of antioxidant capacity, immune function, and intestinal microbes. Results The results showed that resveratrol supplementation increased the number of live births by 13.24 and 26.79% in the first and second phases, respectively, compared with the control group. In the second phase, resveratrol supplementation increased litter weight at weaning and in the concentrations of growth hormone (GH), insulin (INS), progesterone (PROG), triglycerides, and uric acid (UA). The plasma superoxide dismutase (SOD) level on day 110 of gestation and day 14 of lactation, as well as glutathione peroxidase (GSH-Px) on day 14 of lactation in the first phase, showed an increasing trend (p = 0.0728, p = 0.0932, and p = 0.067, respectively) in the resveratrol group, compared with the control group. On day 14 of lactation, the plasma total antioxidant capability (T-AOC) level was higher in the second phase, while the plasma malondialdehyde (MDA) level was lower in both phases in the resveratrol group. Resveratrol supplementation increased the abundance of immunoglobulin A (IgA), immunoglobulin G (IgG), and immunoglobulin M (IgM) in colostrum and the relative abundance of Lactobacillus and Alloprevotella but decreased the relative abundance of Escherichia-shigella in piglet feces in the second phase. In addition, Spearman's correlation analysis indicated that the weight gain of weaned piglets was positively (p < 0.05) associated with IgM content in colostrum and the abundance of Lactobacillus in the fecal microbiota of piglets in the second phase. Moreover, the abundance of Alloprevotella was positively correlated with the contents of IgA and IgG in colostrum, while the abundance of Lactobacillus was positively correlated with IgM content. Conclusion These findings indicated that maternal resveratrol supplementation could enhance the growth performance, antioxidant capacity, and intestinal health of piglets in a high temperature environment, which might be associated with increased immunoglobin secretion from colostrum.